Decade of democracy in Africa - Ndegwa, Stephen N. (Leiden ; Boston : Brill, 2001)
Annotation The democratic experiment in Africa has had a checkered history over the past ten years. Analysts of this process tend to focus on the political and legal space instead of including broader issues such as norms, generational change and class. Authors in this volume argue that African civil society is less likely to support democracy, they measure African democracy by the women's rights movements, unravel the mythical hope of technology and point to ideological capitulation necessary for a limited transition. Past experience from Botswana, South-Africa, Ghana, Kenya, Uganda and Madagascar will give the readers an understanding of democracy in Africa.
A Decade of Democracy in Africa / Stephen N. Ndegwa -- Civil Society in Africa or African Civil Society? / Stephen Orvis -- Women's Rights Movements as a Measure of African Democracy / Judith Van Allen -- Ideology, Political Education, and South Africa's Transition from Apartheid / Nigel Gibson -- Gender, Development, and Democratization in Africa / Lisa Aubrey -- Popular Definitions of Democracy from Uganda, Madagascar, and Florida, U.S.A. / Richard R. Marcus, Kenneth Mease, Dan Ottemoeller -- Information Technology and Democratic Participation in Africa / Wisdom J. Tettey.
Includes bibliographical references and index.
committed to retain
Keywords: Democracy -- Africa; Democratization -- Africa; Civil society -- Africa; Civil society; Democracy; Women's rights; Africa